(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
A Fourteen day experimental study was carried out to determine the day of highest glucoamylase activity using amylopectin from guinea corn starch as the sole carbon source. Two peaks of high activity were observed on the fifth and twelveth days, and were thus mass produced. Specific activities for crude enzymes were found to be 729.45 U/mg and 1046.82 U/mg for day five and twelve harvested enzymes respectively. Ammonium sulphate saturations, 70% and 20%, were found suitable to precipitate proteins with highest glucoamylase activity for day five and twelve harvested enzymes respectively. After ammonium sulphate precipitation and gel filtration, specific activities were found to be 65.98 U/mg and 180.52 U/mg respectively for day five harvested enzyme and 61.51 U/mg and 272.81 U/mg for day twelve harvested enzyme. The pH optimum for day five harvested enzyme were found to be 7.5, 7.5 and 6.0 using tiger nut, cassava and guinea corn starches as substrates respectively, also, the pH optimum for day twelve harvested enzyme were found to be 5.0, 8.5 and 7.0 using tiger nut, cassava and guinea corn starches as substrate, respectively. Optimum temperatures were found to be 50˚C and 45˚C for day five and twelve harvested enzymes, respectively. Km and Vmax, of day five harvested enzyme were found to be 770.75 mg/ml and 2500 μmol/min, 158.55 mg/ml and 500 μmol/min and 46.23 mg/ml and 454.53 μmol/min using cassava, guinea corn and tiger nut starches as substrate respectively. Km and Vmax of day twelve harvested enzyme were found to be 87.1 mg/ml and 384.61 μmol/min, 29.51 mg/ml and 243.90 μmol/min, and 2364 mg/ml and 2500 μmol/min, using cassava, guinea corn and tiger nut starches as substrate respectively. Bangladesh J. Sci. Ind. Res. 52(4), 263-272, 2017